Return of Kyz-Jibek to glorify friendship and love - Shamatov, Duishon (My University, 2015)
Poem of Kyz-Jibek a manuscript of 101 pages hand-written by a Kazakh political prisoner of KARLAG in Karaganda during the Stalin's period.
(Story of a manuscript from KARLAG)
Keywords: Kyz-Jibek; Poem of Kyz-Jibek; KARLAG; Küzöbay Kuranov; Ashimkhan Zhampeisov; Қыз Жібек